Lipopolysaccharide (LPS)-induced dopamine cell loss in culture: roles of tumor necrosis factor-α, interleukin-1β, and nitric oxide - Gayle, Dave A; Ling, ZaoDung; Tong, ChongWai; Landers, Teresa; Lipton, Jack W; Carvey, Paul M (Brain research. Developmental brain research, 2002)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the loss of dopamine (DA) neurons of the substantia nigra pars compacta (SNc). Although the exact mechanisms responsible for this cell loss are unclear, emerging evidence suggests the involvement of inflammatory events. In the present study, we characterized the effects of the proinflammatory bacteriotoxin lipopolysaccharide (LPS) on the number of tyrosine hydroxylase immunoreactive (THir) cells (used as an index for DA neurons) in primary mesencephalic cultures. LPS (10–80 μg/ml) selectively decreased THir cells and increased culture media levels of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) as well as nitrite (an index of nitric oxide (NO) production). Cultures exposed to both LPS and neutralizing antibodies to IL-1β or TNF-α showed an attenuation of the LPS-induced THir cell loss by at least 50% in both cases. Inhibition of the inducible form of nitric oxide synthase (iNOS) by l-NIL did not affect LPS toxicity, but increased the LPS-induced levels of both TNF-α and IL-1β. These findings suggest that neuroinflammatory stimuli which lead to elevations in cytokines may induce DA neuron cell loss in a NO-independent manner and contribute to PD pathogenesis.